Clinical Research in the NHS Today - Dickinson, C J (J R Coll Physicians Lond, 1994)
Most members of the British Medical Research Society who replied to a postal questionnaire survey think that clinical research in Britain is in decline. Research by NHS staff is being discouraged by hospital managers. Increasing service and managerial work by academic and research, staff is curtailing research activity. Recruitment of academic physicians is being adversely affected. Collaborative research between hospitals and research, made possible by tertiary referral, is under increasing threat. This impoverishes the clinical service for rare diseases and complex medical and surgical problems. Most respondents expect the situation to get worse. Ways must be found to protect clinical research before more research teams are irrevocably damaged or broken up. Commissioning of some 'new blood' senior lecturers would be the best way to improve things, and would greatly raise morale.